MY SERVANT’S AND MY MAIDSERVANT’S RIGHT - Șchiopu-Constantin, Gheorghe (Sacra scripta, 2019)
Job 31: 13-15 refers to Job's attitude toward the right of his slaves. As an act of honor, stemming from the sense of honor and respect for created beings, Job accepted to go to court with his slaves when they accused him. In these verses, we can see how a master of slaves, clothed in the clothes of righteousness and fairness (Job 29:14), responds to their allegations with respect and, at the same time, obeys the sentence in the courtroom, even though it might be unfavorable.